Pengelolaan Zakat dan Wakaf di Malaysia dan Turki: Studi Komparatif - Adrianna Syariefur Rakhmat; Irfan Syauqi Beik (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This paper aims to analyze the management of zakat and waqf in Malaysia and Turkey. This study uses a descriptive-comparative analysis method to describe the similarities and differences in the management of zakat and waqf between Malaysia and Turkey. The results of this study include that zakat in Malaysia is mandatory, while zakat in Turkey is voluntary. Zakat in Malaysia and Turkey are both tax deductible. The Government of Malaysia is involved in the management of zakat, while the Government of Turkey does not participate in the management of zakat. The Government of Malaysia and Turkey both participate in the management of waqf. The ministry involved in waqf management in Malaysia is the ministry of religion, while the ministry involved in waqf management in Turkey is the Ministry of Culture and Tourism. Secularism has a negative influence on the practice of waqf in Malaysia and Turkey. The issue of waqf that should have been handled in a sharia court, however, turned out to be handled by a civil court. Meanwhile, the change in the term waqf to ta'sis in Turkey has resulted in a decrease in the number of waqf collections.